PEMEROLEHAN FONOLOGI PADA ANAK USIA 4 TAHUN: STUDI KASUS YWA (KAJIAN PSIKOLINGUISTIK) - Saputri, Seza Riski (University of Brawijaya, 2023)
This research aims to describe the phonological acquisition of 4 years old child with the initials YWA and the factors that influence of YWA’s phonological acquisition. This research is a qualitative descriptive type. The data collection method used in this research is observation method and conversation method. The observation method is realized with the basic tapping technique and advanced observation of involved conversation technique and taking note technique. The conversation method is realized with the basic stimulation technique and advanced face to face technique. The data analysis method used in this research is matching method with the basic sort determinant elements technique and advanced comparison equalize and differentiate techniques. The method of presenting a result of data analysis used in this research is a formal and informal method. The result of data analysis show that at the 4 years old, YWA’s able to pronounce vocoid phons [i], [I], [e], [«], [a], [u], [U], [o], [¿], and [\] and contoid phons [p], [b], [t], [d], [k], [g], [Ö], [c], [j], [s], [z], [h], [m], [n], [÷], [w], [y], [q], [r], and [v]. Contoid phons [f], [l], and [n ] is able to pronounce. But at the certain of vocabulary, those phons hasn’t been able to be pronounce correctly. The factors that influence of YWA’s phonological acquisition is consist of physical readiness, mental readiness, imitation, opportunities to train and practice, motivation, guidance, and phon closeness. Keywords: psycholinguistics, language acquisition, phonological acquisition